Crustal movements and gravity - Rodríguez Pujol, Enrique (Física de la Tierra, 2012)
Gravity time variation interseismic rates differ globally, regionally and locally if they are measured in active regions or in stable regions. In the long run, gravity in the surface of the earth changes with time mainly due to the slow vertical movements of the earth crust, tectonic faults and especially, in regions close to the plate boundaries. In non-active regions gravity change rates are about 0-0.4 microGal/year (0-1.2mm/year) while unveiling in active regions rates about 1-4 microGal/year (2-12 mm/year). Absolute gravity measurements can give us valuable information about interseismic vertical displacements of the earth crust.
Keywords: gravity; crust; geodynamics; time series; seismotectonics; GPS; Geodesy.